Characterizations of the Set Less Order Relation in Nonconvex Set Optimization - Jahn, Johannes (Journal of Optimization Theory and Applications, 2022)
For nonconvex set optimization problems based on the set less order relation, this paper presents characterizations of optimal sets and gives necessary conditions for set inequalities and non-optimal sets using directional derivatives. For specific order cones, the directional derivatives of known functionals describing the negative cones are also given.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Necessary conditions; Set less order relation; Set optimization